Outcomes with IV/oral Delafloxacin (DLX) Compared with Vancomycin/Aztreonam (VAN/AZ) in Treatment of Patients with Acute Bacterial Skin and Skin Structure Infections (ABSSSI) and Gram-negative (GN) Pathogens. (4th October 2017) - O'Riordan, William; Overcash, Scott; Lawrence, Laura; McCurdy, Sandra P; Tseng, Carol; Cammarata, Sue K
Abstract: Background: DLX, an anionic fluoroquinolone antibiotic is in development for treatment of ABSSSI. This analysis focuses on patients with Gram-negative pathogens from 2 phase 3 ABSSSI trials. Methods: 2 double-blind trials of adults with ABSSSI randomized patients 1:1 to receive either IV/oral DLX monotherapy or VAN 15 mg/kg with AZ for 5 – 14 days, conducted in US, Europe, Latin America and Asia. Key endpoints were objective response at 48–72 hours and investigator assessment of outcome at Follow-up (FU day 14) and Late Follow-up (LFU day 21–28). Results: In the 2 studies, 1042/1510 patients enrolled had a pathogen at baseline (Micro Intent to Treat [MITT]). 197 patients (19%) had a GN pathogen isolated at baseline; most were part of a mixed infection. 66% were male, mean age 52 yrs. Median digital erythema area at baseline was ~227 cm 2 . 25% had cellulitis, 27% abscesses, and 47% wound infections.The most common location was the lower extremities. K. pneumoniae was the most frequent GN isolate. The MIC50, MIC90 and MIC range were 0.12, 0.25, 0.03–4 µg/mL for K. pneumoniae ; 0.12, 2, 0.03->8 µg/mL for E. cloacae ; 0.06, 4, 0.008–4 µg/mL for E. coli ; and 0.25, 4, 0.12->8 µg/mL for P. aeruginosa . Key endpoints are shown below: In the overall population, the proportion of patients with at least one treatment-emergent AE (TEAE) was similar for DLX (45.1%) compared with VAN/AZ (47.7%). The most frequent treatment-related adverse events were gastrointestinal in nature including nausea seen in 6.1% and 4.3% and diarrhea seen in 6.1% and 2% of DLX and VAN/AZ patients respectively. There were 0.8% of DLX patients and 2.4% VAN/AZ patients who discontinued treatment due to treatment related AEs. Conclusion: GN pathogens are a consideration in ABSSSI antibiotic selection. Fixed dose DLX monotherapy was comparable to VAN/AZ in effects in patients with GN pathogens based on the early and investigator assessed response and micro response. DLX appears effective and well tolerated in patients with GN pathogens in ABSSSI. Disclosures: W. O'Riordan, Melinta: Investigator, Research grant; S. Overcash, Melinta: Investigator, Research grant; L. Lawrence, Melinta: Employee, Salary; S. P. McCurdy, Melinta Therapeutics: Employee, Salary; C. Tseng, Melinta: Consultant and Research Contractor, Consulting fee; S. K. Cammarata, Melinta Therapeutics: Employee, Salary